Correlation between morphological features of the anterior cruciate ligament: A quantitative study using a porcine model - Wang, Huizhi; Zhang, Zhuoyue; Shi, Qinyi; Zeng, Yi-Ming; Cheng, Cheng-Kung (Frontiers in Veterinary Science, 2023)
This study aimed to explore the quantitative correlation between morphological features of the anterior cruciate ligament (ACL), thus to provide useful information for improving anatomical reconstruction techniques and designing artificial ligaments. 19 porcine knees were fixed at full extension using 10% formalin and were dissected to expose the ACL. ACL lengths were measured using a caliper. Mid-substances of the ACL were cut and scanned using X-ray microscopy, and the cross-sectional area (CSA) was measured at the isthmus. Margins of direct and indirect bone insertion sites were distinguished and marked. Measurements were performed on digital photographs to obtain the areas of bone insertions. Statistical analysis using nonlinear regression was used to identify potential correlations among the measurements. The results showed that the CSA at the isthmus was significantly correlated with the total area of the bone insertion sites and the area of tibial insertion. The area of the tibial insertion was significantly correlated with the area of its direct insertion site. In contrast, the area of the femoral insertion was significantly correlated with the area of its indirect insertion site. The area of the indirect tibial insertion showed a weak correlation with the length of ACL, whereas the length of the ACL was not able to predict or be predicted by any other parameters. In conclusion, the CSA at the ACL isthmus is more representative for assessing the size of the ACL. However, ACL length has little correlation with the CSA of the isthmus or bone insertion sites, and thus should be evaluated independently for ACL reconstruction.